Phase Ib and pharmacokinetics study of alpelisib, a PIK3CA inhibitor, and capecitabine in patients with advanced solid tumors - Lim, Ah Reum; Kim, Boyeon; Kim, Jwa Hoon; Hyun, Myung Han; Park, Kyong Hwa; Kim, Yeul Hong; Lee, Soohyeon (Frontiers in Oncology, 2024)
Background: This phase Ib study was performed to determine the safety of combination capecitabine with alpleisib (phosphatidylinositol 3-kinase catalytic subunit p110α blockade) and determine the maximal tolerated dose (MTD) and recommended phase ll dose (RP2D) of this combination regimen in patients with advanced solid tumors refractory to standard therapy. The synergistic anti-tumor activity and pharmacokinetics (PK) were investigated.Methods: Dose escalation phases were conducted in patients with advanced solid cancers who were refractory to standard therapy regardless of PIK3CA mutation. Patients were administered orally once daily alpelisib (200mg and 300mg) and twice daily capecitabine (850mg, 1000mg, 1250mg orally, days 1-14) every 3 weeks. Standard "3+3" dose escalation was used to define the MTD. The effect of alpelisib on the PK of capecitabine was assessed.Results: Patients with 6 colorectal cancer (three PIK3CA mutation) and 6 breast cancer (all PIK3CA mutation) were enrolled. The first three patients in dose level 0 (alpelisib 200mg daily, capecitabine 1,000 mg/m 2 twice daily) had no dose-limiting toxicities (DLTs). In dose level 1 (alpelisib increased to 300 mg daily, capecitabine 1,000mg twice daily), one of six patients had DLT (grade (Gr) 3 hyperglycemia). When dose level 2 (alpelisib 300mg daily, capecitabine 1,250 mg/m 2 twice daily) was expanded to 3 patients, no patients had DLTs. The combination of alpelisib 300mg daily and capecitabine 1,250 mg/m 2 twice daily was declared as the MTD/RP2D in patients with advanced solid tumors. The most common AEs were Gr 1-3 hyperglycemia (75.0%). Frequent all-grade, treatment-related AEs included Gr 2-3 nausea (75.0%), Gr 1-2 diarrhea (50.0%), Gr 1-2 hand-foot syndrome (41.7%), Gr 1-2 anorexia (41.7%), Gr 2 mucositis (33.3%). Antitumor activity was observed in patients with PIK3CA mutant breast cancer (3 partial response and 3 stable disease of total 6 patients). Alpelisib exposure (Cmax and AUC0-12) was unaffected by concomitant capecitabine. There were no clinically relevant drug-drug interactions observed between alpelisib and capecitabine. Conclusions: The combination of alpelisib and capecitabine is generally tolerated, without pharmacokinetic interactions, and shows antitumor activity in patients with PIK3CA mutant advanced cancers.